Jubran Khalil Jubran’s wisdoms (quotes) and their symmetries in Wisam Al Haddad's ceramics (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research addressesJubran Khalil’s wisdoms (quotes) and their symmetry in the ceramics of Wisam Al Haddad.The research is composed of four chapters;the first chapteraddresses the methodological framework for the researchrepresented by the research problem and its importance, which ends with the following question: - Are there symmetriesof Gibran Khalil Gibran’s wisdoms in the ceramics of Wisam Haddad?The significance of research:Highlighting aremarkable figure in the history of Arabic poetry, namely, Gibran KhalilGibran.Enriching art libraries with a study of one of the cognitive concepts regarding quotes and their inspiration inceramics . Finally, presenting to all humanity a tremendous heritage that is still a focus of attention of researchers andartists in this field.